Respuesta :

Answer:

1. x= 3y+6/2

y=2/3x-2

2.x=−y+3

y=−x+3

Step-by-step explanation:

1. Let's solve for x.

y=2/3x-2

Step 1: Flip the equation.

2/3x-2=y

Step 2: Add 2 to both sides.

2/3x-2+2=y+2

2/3x=y+2

Step 3: Divide both sides by 2/3.

2/3x/2/3=y+2/2/3

x= 3y+6/2

Let's solve for y.

y=2/3x-2

2. Let's solve for x.

y=−x+3

Step 1: Flip the equation.

−x+3=y

Step 2: Add -3 to both sides.

−x+3+−3=y+−3

−x=y−3

Step 3: Divide both sides by -1.

-x/-1=y-3/-1

x=−y+3

Let's solve for y.

y=−x+3

here are two graphs if you need a better explanation

HOPE THIS HELPS

Ver imagen Аноним
Ver imagen Аноним